Dampak Profitabilitas, Leverage, Ukuran Perusahaan Dan Kesempatan Bertumbuh Terhadap Earning Response Coefficient - Norotus Sa'diyah; Siti Aliyah; Subadriyah; Solikhul Hidayat (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
This study aims to determine the effect of profitability, leverage, company size and growth opportunities on the earning response coefficient of mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The data used in this research is secondary data. The population in this study are all mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sampling technique used purposive sampling technique which was selected based on predetermined criteria, so that a sample of 55 data was obtained. The method used in this research is multiple linear regression analysis. This study uses a tool that is IBM SPSS Statistics 20 software program. The results of this study indicate that profitability has a significant positive effect on the earning response coefficient, leverage has a significant negative effect on the earning response coefficient, company size and growth opportunities have no effect on the earning response coefficient.